2003
DOI: 10.1113/jphysiol.2003.043091
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis decreases low Ca2+ ‐induced neuronal excitation by inhibiting the activity of calcium‐sensing cation channels in cultured mouse hippocampal neurons

Abstract: The effects of extracellular pH (pHo) on calcium‐sensing non‐selective cation (csNSC) channels in cultured mouse hippocampal neurons were investigated using whole‐cell voltage‐clamp and current‐clamp recordings. Decreasing extracellular Ca2+ concentrations ([Ca2+]o) activated slow and sustained inward currents through the csNSC channels. Decreasing pHo activated amiloride‐sensitive transient proton‐gated currents which decayed to baseline in several seconds. With proton‐gated channels inactivated by pre‐perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 67 publications
(97 reference statements)
6
29
0
Order By: Relevance
“…Primary Neuronal Culture-Primary cortical neuronal cultures were prepared from embryonic Swiss mice at 16 days of gestation according to our previously described method (10,23). In brief, the brains of embryos were rapidly removed and incubated in Ca 2ϩ -and Mg 2ϩ -free ice-cold phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary Neuronal Culture-Primary cortical neuronal cultures were prepared from embryonic Swiss mice at 16 days of gestation according to our previously described method (10,23). In brief, the brains of embryos were rapidly removed and incubated in Ca 2ϩ -and Mg 2ϩ -free ice-cold phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiology-Whole cell patch clamp recordings were performed as described previously (10,23). Patch pipettes were pulled by a two-step puller (PP83; Narishige, Tokyo, Japan) from thin wall borosilicated glass (1.5 mm diameter; WPI, Sarasota, FL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main expansion of our model compared to its previous versions was the implementation of the Casensitive nonselective cation conductance, g NSCC , (based on data given in Chu et al 2003;Xiong et al 1997 and Xiong, personal communication). The nonspecific cation channel senses the extracellular calcium concentration ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Hablitz et al (1986) suggested that a similar current in central neurons could play a role in the generation of seizures and spreading depression (SD). MacDonald, Xiong, and collaborators (Chu et al 2003;Xiong and MacDonald 1999;Xiong et al 1997) detected in mammalian central neurons an NSCC that is activated by the lowering of [Ca 2+ ] o . This channel is maximally open when extracellular calcium concentration is zero, and at the normal [Ca 2+ ] o of 1.2-1.5 mM it permits the flow of a small current which, presumably, adds to the resting conductance of the cell.…”
mentioning
confidence: 98%